Building Tolerance and Openness Through Islamic Education: Addressing Cultural and Religious Pluralism - Al Jumhuri, Muhammad Asroruddin (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study investigates how Islamic education fosters tolerance and openness, especially concerning cultural and religious pluralism, essential for global social cohesion. Islamic education, rooted in rich ethical traditions, can significantly contribute to this endeavor. The research involves a literature review to explore tolerance-building in Islamic education. Qualitative interviews and surveys with educators, students, and community leaders provide insights. Data collection methods include semi-structured interviews and questionnaires, enabling qualitative and quantitative analysis. Thematic analysis identifies recurring patterns in qualitative data, while statistical methods reveal trends in quantitative data. Preliminary findings highlight Islamic education's role in promoting tolerance by emphasizing values like compassion and empathy. Both educators and students see it as fostering intercultural dialogue, promoting inclusivity. This study's implications are significant for policymakers, educators, and community leaders in Islamic education. Recognizing Islamic education's potential in fostering tolerance can lead to more effective strategies and curricula. Cultivating these values ultimately contributes to building resilient societies amidst diversity.